The reminiscences of Thomas Stubbs, 1820 - 1877 - McGeoch, Robert Thomas (Rhodes University, Faculty of Humanities, Department of History, 1965)
The "Reminiscences" of Thomas Stubbs are one of several such compositions which have survived from the 1820 Settlers. The manuscript offers one of the fullest and most lively accounts of frontier life, and the experiences of the Settlers as seen through the eyes of Thomas Stubbs. The object of this thesis has been to reconstruct the life of Thomas Stubbs which has proved an arduous yet absorbing task and to comment upon and evaluate some of the views Stubbs expressed when he wrote the "Reminiscences" between 1874 and 1875, as well as to test, where possible, the validity of the opinions and sentiments formed during a half-century's acquaintance with the Eastern frontier of the Cape of Good Hope.
Keywords: Stubbs family; British settlers of 1820 (South Africa) -- Personal narratives; South Africa -- History -- Frontier Wars, 1811-1878; Cape of Good Hope (South Africa) -- History